2021
DOI: 10.3390/plants11010015
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Antimicrobial and Antioxidant Properties of Thymus zygis L. and Thymus willdenowii Boiss. Essential Oils

Abstract: Essential oils (EOs) are chemical products produced by odoriferous glands from a variety of plants. These essential oils have many health benefits: antiseptic, anti-inflammatory and antimicrobial activities. So due to these medicinal properties, the present study was designed to analyze essential oils of Thymus zygis L. and Thymus willdenowii Boiss. for their chemical composition and biological activities. These two thyme species were collected from the region of Ifrane, Middle Atlas of Morocco. The EO was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Among the tested EOs, the most active is T. broussonetii essential oil with an IC 50 of around 3.48 ± 0.05 μL/mL. The high activity of T. broussonetii essential oil has already been indicated in several works including El Ouariachi et al, Alaoui Jamali et al and El Bouzidi et al, [ 14 , 31 , 41 , 47 ]. T. capitatus EO also demonstrated a high antioxidant power with an IC 50 of 4.88 ± 0.04 μL/mL.…”
Section: Resultsmentioning
confidence: 89%
“…Among the tested EOs, the most active is T. broussonetii essential oil with an IC 50 of around 3.48 ± 0.05 μL/mL. The high activity of T. broussonetii essential oil has already been indicated in several works including El Ouariachi et al, Alaoui Jamali et al and El Bouzidi et al, [ 14 , 31 , 41 , 47 ]. T. capitatus EO also demonstrated a high antioxidant power with an IC 50 of 4.88 ± 0.04 μL/mL.…”
Section: Resultsmentioning
confidence: 89%
“…It serves as a dependable representation of the EO components and acts as an identifying characteristic of the EOs. The chemical makeup of these oils can reflect the special properties of the oils, and GC–MS is a reliable method for determining the purity of EOs in most situations (Radi et al., 2021). The criteria of selection of EO depends on the features of the substance from which the oil will be extracted since they are present in varied parts of the plant, like fruits, leaves, roots, stems, and seeds.…”
Section: Chemical Composition and Biological Activities Of Essential ...mentioning
confidence: 99%
“…Moreover, these bioactive compounds have powerful anti-septic, anti-inflammatory, antibacterial, anti-oxidative, and immune-boosting properties [ 9 ]. A recent study revealed that EOs from thyme species have strong anti-oxidant and anti-microbial activities and showed action against multi-resistant bacteria known as Acinetobacter baumannii [ 10 ]. Another study demonstrated that EOs of citrus hystrix DC.…”
Section: Introductionmentioning
confidence: 99%